Female entrepreneurship and participation rates in 19th century Chile - Bernardita Escobar Andrae (Estudios de Economía, 2015)
This article studies female participation rates as entrepreneurs during the 1877- 1908 period using data from the Santiago business license registry, census data and the trademark registry. The evidence reveals that business women in Santiago increased from 3 to 14 percent of the female labor force in the corresponding sectors analyzed during the period. The evidence shows women increasingly as business people: half of the economic sectors analyzed had female entrepreneurs while firms run by women increased from 13 to 20 percent in Santiago, but reached only 5 percent of national firms within the elite.
Keywords: N86; N96; 330; female entrepreneurship; economic history; economic development; Chile in late 19th century